Application of Bacteriocins in Practice, Including Microcins: the Present and the Future - M. G. Teimurazov; I. M. Kovalenko; O. E. Khokhlova (Антибиотики и Химиотерапия, 2025)
In recent decades, bacteriocins have been actively studied as antimicrobial compounds. Bacteriocins have been primarily used to preserve food, but they are currently of increasing interest as potential clinical antimicrobial agents and possible immunomodulatory agents. Infections caused by antibiotic-resistant bacteria have been declared a global public health threat. Bacteriocins represent a potential solution to this worldwide threat due to their broad- or narrow-spectrum activity against antibiotic-resistant bacteria. In particular, despite their role as natural alternatives to chemical preservation in ensuring food safety, nisin remains the only bacteriocin approved by regulatory authorities for food preservation. The article highlights data on the safety of bacteriocins and their possible toxicity, which may become a barrier to their wider use in medicine and industry. The article describes the latest trends in the development of bacteriocin-based drugs, their effectiveness, spectrum of antimicrobial activity, and mechanisms of action on microorganisms.